1999
DOI: 10.1002/(sici)1097-0177(199912)216:4/5<442::aid-dvdy12>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of two ATP-gated ion channels, P2X5 and P2X6, in developing chick skeletal muscle

Abstract: Physiological and pharmacological studies have shown that ATP has potent effects on developing chick skeletal muscle. These effects have previously been shown to be developmentally regulated, and the responses were characteristic of activation of the P2X ligand‐gated ion‐channel family of ATP receptors. Here, using immunohistochemistry, we describe the expression patterns of two members of the P2X receptor family, P2X5 and P2X6, during development of skeletal muscle in the chick embryo. These receptors were fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 40 publications
(52 reference statements)
3
38
0
Order By: Relevance
“…In the 1990s, cloning studies demonstrated that P2X 5 was expressed in chick skeletal muscle, and when chick P2X 5 was expressed in oocytes, the currents exhibited properties expected for the endogenous chick receptors [41]. However the expression of other P2X receptors (P2X 1 and P2X 6 ) has been detected in chick skeletal muscle [27,29]. Similarly, studies in mammals have revealed a complex expression pattern in skeletal muscle with P2X 1 , P2X 2 , P2X 4 , P2X 5 , and P2X 6 being detected [27,28,33,42], but a clear role for P2X signaling in skeletal muscle has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1990s, cloning studies demonstrated that P2X 5 was expressed in chick skeletal muscle, and when chick P2X 5 was expressed in oocytes, the currents exhibited properties expected for the endogenous chick receptors [41]. However the expression of other P2X receptors (P2X 1 and P2X 6 ) has been detected in chick skeletal muscle [27,29]. Similarly, studies in mammals have revealed a complex expression pattern in skeletal muscle with P2X 1 , P2X 2 , P2X 4 , P2X 5 , and P2X 6 being detected [27,28,33,42], but a clear role for P2X signaling in skeletal muscle has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Although subsequent studies confirmed the existence of ATP-sensitive ion channels in avian skeletal muscle, they suggested that the single-channel currents had a very low unitary conductance compared to the initial report [25,26]. Following the cloning of the P2X family, the expression of multiple P2X receptors by skeletal muscle has been demonstrated in several different organisms [27][28][29][30]. Several roles for P2X receptors in muscle have been proposed including regulating myogenesis during development [28], regeneration of muscle following injury [31,32], and roles in the regulation of muscle fiber contractility [33] and in muscle fiber type specification [34].…”
Section: Cloning Of Zebrafish P2x Receptor Cdnas Uncovered Three New mentioning
confidence: 99%
“…The RNA is expressed predominantly in heart (Garcia-Guzman et al, 1996) but there is also expression in brain, spinal cord, and adrenal gland (GarciaGuzman et al, 1996). Immunoreactivity for P2X 5 subunits has also been described in developing skeletal muscle of the rat (Meyer et al, 1999;Ryten et al, 2001); recently, the receptor has been implicated in the differentiation of satellite cells into mature multinucleated muscle fibers (Ryten et al, 2002). Mammalian skin and endocrine (Glass and Burnstock, 2001) cells also show P2X 5 immunoreactivity.…”
Section: Introductionmentioning
confidence: 98%
“…The expression and immunoreactivity of P2X6R mRNA are seen throughout the central nervous system, including Purkinje cells in the cerebellum and pyramidal cells in the hippocampus Rubio and Soto, 2001;Burnstock and Knight, 2004). Expression of this receptor has also been reported in sensory ganglia , skeletal muscle (Meyer et al, 1999), uterus and granulose cells of the ovary , thymus (Glass et al, 2000), and the human salivary gland (Worthington et al, 1999). Up-regulation of this receptor has been detected in human heart tissue from patients with congestive heart failure (Banfi et al, 2005).…”
mentioning
confidence: 99%